PENGARUH KOMPETENSI PEMBUKUAN, RISIKO PEMERIKSAAN, DAN PATRIOTISME EKONOMI TERHADAP KEPATUHAN WAJIB PAJAK - Adiningtyas, Rachmatika; Zulaikha, Zulaikha (Diponegoro Journal of Accounting, 2016)
This study aimed to analyze the effect of bookkeeping competence, tax audit risk, and economic patriotism on tax compliance. The research model adopts the Theory of Planned Behavior to explain the factors that influence the intention of behaving to comply the duty of tax associated with the variables that influence it.Respondents in this study is an individual taxpayer of micro, small and medium enterprises listed on KPP Pratama Kota Semarang. The data collection is done by randomly selecting 4 of 8 KPP Pratama in Semarang for further surveys directly on micro, small and medium enterprises. Those KPP is KPP Pratama Semarang Barat, KPP Pratama Semarang Selatan, KPP Pratama Semarang Tengah 1, and KPP Semarang Tengah 2. The analysis technique used is the technique of multiple regression analysis with data obtained from direct surveys using questionnaires media and retrieval techniques sample used is convenience sampling.Of the 300 questionnaires distributed, 286 questionnaires received back, and as many as 277 questionnaires could be used for research. The result if this study shows that the competence bookkeeping and economic patriotism positive and significant impact on tax compliance. While the risk of tax audits and significant negative effect on tax compliance.